2022
DOI: 10.1200/go.22.00104
|View full text |Cite
|
Sign up to set email alerts
|

Germline Pathogenic Variant Prevalence Among Latin American and US Hispanic Individuals Undergoing Testing for Hereditary Breast and Ovarian Cancer: A Cross-Sectional Study

Abstract: PURPOSE To report on pathogenic germline variants detected among individuals undergoing genetic testing for hereditary breast and/or ovarian cancer (HBOC) from Latin America and compare them with self-reported Hispanic individuals from the United States. METHODS In this cross-sectional study, unrelated individuals with a personal/family history suggestive of HBOC who received clinician-ordered germline multigene sequencing were grouped according to the location of the ordering physician: group A, Mexico, Centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 79 publications
4
20
1
Order By: Relevance
“…The reclassifications are feasible due to the accumulation of larger genome databases and additional supporting evidence. Similarly, variant reclassification has been reported in ancestry‐based studies in underrepresented and diverse ethnic backgrounds 39,49–53 . Therefore, large prospective genetic studies are needed to assess the larger reclassification of variants in Turkish and other populations.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The reclassifications are feasible due to the accumulation of larger genome databases and additional supporting evidence. Similarly, variant reclassification has been reported in ancestry‐based studies in underrepresented and diverse ethnic backgrounds 39,49–53 . Therefore, large prospective genetic studies are needed to assess the larger reclassification of variants in Turkish and other populations.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, variant reclassification has been reported in ancestry-based studies in underrepresented and diverse ethnic backgrounds. 39,[49][50][51][52][53] Therefore, large prospective genetic studies are needed to assess the larger reclassification of variants in Turkish and other populations. Furthermore, the development of large gnomAD-like databases representing the Turkish population and making such knowledge bases publicly available is a crucial next step in addressing the current limitations.…”
Section: F I G U R Ementioning
confidence: 99%
“…Table 1 lists the most common pathogenic BRCA variants in the Asian population. We tested the ethnic specificity of the 1762 Asian pathogenic BRCA variants by comparing them with the reported ones with clear ethnic origin information, including the 431 pathogenic BRCA variants collected from the Latino/Hispanic American population, 16 and the 466 pathogenic BRCA variants identified from Middle Eastern, North African and South European countries. 49 The results showed that only 192 of the 431 variants were shared accounting for 10.9% of the 1762 Asian pathogenic BRCA variants or 44.5% of the 431 Latin/Hispanic pathogenic BRCA variants (Figure 3A and Tables S8A‐S8C ); and only 264 of the 466 variants were shared accounting for 15% of the 1762 Asian pathogenic BRCA variants and 56.7% of the 466 pathogenic BRCA variants from Middle Eastern, North African and South European countries (Figure 3B and Tables S8D‐S8F ).…”
Section: Resultsmentioning
confidence: 99%
“…It is well determined that human BRCA variation is highly ethnic‐specific in human populations 9‐21 . Like in many human genetic studies, 22 however, the majority of current BRCA variation data were derived from the European descendant populations 23‐25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation